Cardiac magnetic resonance and B-natriuretic peptide are superior prognostic tools to guideline-based echocardiography in asymptomatic patients with chronic severe aortic regurgitation. (25th November 2020) - Kockova, R; Linkova, H; Hlubocka, Z; Blaha, M; Tuna, M; Medilek, K; Lupinek, P; Sedmera, D; Penicka, M
Abstract: Background: The optimal timing of intervention in patients with chronic aortic regurgitation (AR) is currently based on patient symptoms and echocardiography derived parameters. The sensitivity of this approach is suboptimal and late operation often results in irreversible myocardial damage. Purpose: To determine the prognostic value of novel parameters in asymptomatic patients with chronic severe AR in optimal timing of aortic valve surgery. Methods: Consecutive patients with chronic severe AR not indicated for surgery per the current guidelines were studied in a prospective design in 5 centers. Baseline examination consisted of B-natriuretic peptide (BNP) measurement, comprehensive echocardiography (ECHO) including 3-dimensional (3D) study with vena contracta area (VCA), and complex magnetic resonance (MRI) including regurgitant volume (RV), regurgitant fraction (RF), global myocardial work efficiency (GWE) and extracellular volume (ECV); all analyzed in core lab. All patients were followed every 6 months and the endpoint was disease progression defined as an indication for surgery. The perioperative myocardial biopsy was performed in all surgically treated patients for histological myocardial fibrosis quantification. Results: In total, 129 patients were enrolled between 2015 and 2019, the endpoint occurred in 35 patients during a mean follow-up of 1044 days. Baseline clinical data did not differ between patients with disease progression (surgical group) and stable patients. Baseline BNP levels were higher in the surgical group (63 vs. 20, P<0.01) and a cut-off value of 30.4 ng/L was predictive of disease progression with AUC 0.75. None of the standard ECHO parameters of left ventricular (LV) size and function was predictive of the endpoint. Novel ECHO parameter 3D VCA was higher in the surgical group (32 vs. 26 mm 2, P=0.037). All MRI parameters of LV size and function were predictive of disease progression (all P<0.02), except LV ejection fraction. MRI-derived RV (57 vs. 37 ml, P<0.01) and RF (46 vs. 34%, P<0.01) were identified as the strongest independent predictors of surgery. There was no difference in ECV between the surgical group and stable patients (24 vs. 24, P=0.81) despite a good correlation with histological quantification of myocardial fibrosis. Conclusions: Standard ECHO parameters cannot reliably predict the need for surgery in asymptomatic aortic regurgitation patients. Baseline BNP levels above 30.4 ng/L predict disease progression. Novel imaging parameters – ECHO-derived 3D VCA and MRI-derived parameters of LV size and AR severity might be useful in optimal timing determination. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Ministry of Health of the Czech Republic